Civil war onset, natural resource rents and social cohesion - El-Badawi, Ibrahim; Ibrahim, Hosam; Zaki, Chahir (Economic Research Forum, 2020)
This paper examines the nexus between civil war onset, natural resource rents, and social cohesion. Indeed, the main hypothesis is centered on the role of the hydrocarbon resource in promoting conflicts, especially in societies characterized by discrimination. Hence, using a comprehensive dataset, this paper’s contribution is twofold. First, we test the non-linear effect of institutions and rents on the likelihood of civil war onset. Second, we introduce several measures of social cohesion and institutions. Our main findings show that both political institutions and rents have a non-linear effect on the outbreak of civil wars. Moreover, social cohesion variables measured by the share of discriminated population increases the probability of a civil war onset. These results remain robust in different econometric specifications, various estimation techniques and diverse measures.